Influence of milk, chicken residues and oxygen levels on biofilm formation on stainless steel, gene expression and small RNAs in Salmonella enterica. (August 2018) - Lamas, Alexandre; Regal, Patricia; Vázquez, Beatriz; Miranda, José Manuel; Cepeda, Alberto; Franco, Carlos Manuel
Abstract: Salmonella spp. are highly versatile foodborne pathogens as they can adapt and shift from the aerobic environment outside the host to the anaerobic environment inside the host through changes in gene expression. These changes can be mediated by small RNAs (sRNAs), a class of post-transcriptional regulators that can modulate diverse functions from biofilm formation to motility and virulence. In this study, biofilm formation on stainless steel, motility, morphotype, and transcription of biofilm- and virulence-related genes and sRNAs were evaluated in fourteen Salmonella enterica strains under aerobiosis, microaerobiosis and anaerobiosis conditions. In order to mimic actual food industry conditions and to compare with laboratory media, chicken exudate and milk were used as culture media. In all growth media tested, biofilm formation was significantly greater (P < 0.05) in aerobiosis than in microaerobiosis or anaerobiosis. The RDAR (red, dry, and rough) morphotype was only produced in aerobiosis, while motility was significantly higher in anaerobiosis (P < 0.05) than in microaerobiosis or aerobiosis. Whereas the gene csgD, which codifies the biofilm master regulator, was downregulated, the virulence genes hilA and invA were upregulated in microaerobiosis and anaerobiosis in all growth media. The transcription of sRNAs was highly influenced by both atmosphere and growth media. Positive regulators of biofilm formation arcZ, sroC and csrB were downregulated in microaerobiosis and anaerobiosis in comparison to aerobiosis. Curiously, the negative regulators of biofilm formation oxyS and rprA were also downregulated in microaerobiosis and anaerobiosis. However, the virulence promoter and negative regulator of biofilm formation dsrA was significantly upregulated in chicken juice. The results of this study indicate that oxygen levels have a considerable influence on biofilm formation and motility in Salmonella. Modification of the gene expression and transcription of sRNAs could be useful in understanding how Salmonella adapt to different conditions within the food chain. This information could then be taken into account in the development of new strategies with which to control the growth of this pathogen. Highlights: Anaerobiosis significantly increased the motility of Salmonella strains. Salmonella biofilm formation in stainless steel was influenced by food residues. Virulence genes were significantly upregulated in anaerobiosis in chicken meat juice. Small RNAs transcription was highly influenced by atmospheres and food residues. Small RNAs that enhance biofilm formation were less transcribed in anaerobiosis.